The Cost-Effectiveness of Congenital Adrenal Hyperplasia Newborn Screening in Brazil: A Comparison Between Screened and Unscreened Cohorts - Miranda, Mirela Costa de; Haddad, Luciana Bertocco de Paiva; Trindade, Evelinda; Cassenote, Alex; Hayashi, Giselle Y.; Damiani, Durval; Costa, Fernanda Cavalieri; Madureira, Guiomar; Mendonca, Berenice Bilharinho de; Bachega, Tania A. S. S. (Frontiers in Pediatrics, 2021)
BACKGROUND: Newborn screening for congenital adrenal hyperplasia (CAH-NBS) is not yet a worldwide consensus, in part due to inconclusive evidence regarding cost-effectiveness because the analysis requires an understanding of the short- and long-term costs of care associated with delayed diagnosis. OBJECTIVE: The present study aimed to conduct a cost-effectiveness analysis (CEA) to compare the costs associated with CAH-NBS and clinical diagnosis. METHODS: A decision model comparing the two strategies was tested by sensitivity analysis. The cost analysis perspective was the public health system. Unscreened patients’ data were extracted from medical records of Hospital das Clinicas, Sao Paulo, and screened data were extracted from the NBS Referral Center of São Paulo. The population comprised 195 classical patients with CAH, clinically diagnosed and confirmed by hormonal/CYP21A2 analysis, and 378,790 newborns screened during 2017. Adverse outcomes related to late diagnosis were measured in both cohorts, and the incremental cost-effectiveness ratio (ICER) was calculated. We hypothesized that CAH-NBS would be cost-effective. RESULTS: Twenty-five screnned infants were confirmed with CAH (incidence: 1:15,135). The mortality rate was estimated to be 11% in unscreened infants, and no deaths were reported in the screened cohort. Comparing the unscreened and screened cohorts, mean serum sodium levels were 121.2 mEq/L (118.3–124.1) and 131.8 mEq/L (129.3–134.5), mean ages at diagnosis were 38.8 and 17 days, and hospitalization occurred in 76% and 58% of the salt-wasting patients with the in the two cohorts, respectively. The NBS incremental cost was US$ 771,185.82 per death averted, which yielded an ICER of US$ 25,535.95 per discounted life-year saved. CONCLUSIONS: CAH-NBS is important in preventing CAH mortality/morbidity, can reduce costs associated with adverse outcomes, and appears cost-effective.